2011
DOI: 10.1007/s00421-010-1802-2
|View full text |Cite
|
Sign up to set email alerts
|

Endurance exercise training ameliorates insulin resistance and reticulum stress in adipose and hepatic tissue in obese rats

Abstract: Obesity-induced endoplasmatic reticulum (ER) stress has been demonstrated to underlie the induction of obesity-induced JNK and NF-κB activation inflammatory responses, and generation of peripheral insulin resistance. On the other hand, exercise has been used as a crucial tool in obese and diabetic patients, and may reduce inflammatory pathway stimulation. However, the ability of exercise training to reverse endoplasmatic reticulum stress in adipose and hepatic tissue in obesity has not been investigated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
3
29

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 34 publications
3
68
3
29
Order By: Relevance
“…1 demonstrated that animals receiving high-fat diet and submitted to swimming training reduced both inflammatory proteins (i.e., JNK, IkB, NF-kB) and ER stress (i.e., PERK phosphorylation and elF2alpha) in adipose and hepatic tissues 1 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 demonstrated that animals receiving high-fat diet and submitted to swimming training reduced both inflammatory proteins (i.e., JNK, IkB, NF-kB) and ER stress (i.e., PERK phosphorylation and elF2alpha) in adipose and hepatic tissues 1 …”
Section: Discussionmentioning
confidence: 99%
“…However, some disturbances that culminate in increased immature protein synthesis, which produces unfolded and misfolded proteins, may lead to an adaptive response known as the unfolded protein response (UPR) 1,2 . An imbalance between the load and the ability to fold proteins is defined as the ER stress, occurring physiological changes in UPR signaling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, even though there was no reduction in body weight and adipose tissue, mRNA levels of pro-opiomelanocortin (POMC) were Once enhanced insulin activity in several tissues that are responsible for the metabolic control, the serum levels of pro-inflammatory proteins [65,67], and fasting glucose [61,72] are reduced. After 8 weeks of endurance training, da Luz et al…”
Section: Fructose Consumption and Its Complicatons: The Role Of Aerobmentioning
confidence: 99%
“…The same study also found decreased levels of proteins involved in gluconeogenesis, such as PEPCK and glucose-6-phosphatase (G6Pase). Aerobic exercise also proved to be able to reduce the phosphorylation of proteins kinase RNA-like endoplasmic reticulum kinase (PERK) and eukaryotic initiation factor 2-α (eIF2α) [65], which are regarded as the greatest stress markers of endoplasmic reticulum [69]. Thus, the phosphorylation of insulin receptor tyrosine and their substrates and activation of protein kinase B (Akt) increased as well as decreased inflammation in this tissue.…”
mentioning
confidence: 99%